(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Several surveys on Information Science recurrently indicate the existence of a new field of study in economics, named information economy. According to the information impact perspective, observed along with activation procedures of organization development, from the performance, expansion, penetration and consolidation point of view on the referred market, enhancing information as a market product affects the criterion analysis sine qua non of its research procedures and use. This study corroborates the hypothesis that these studies enable enlightenment on which information flow leads company managers to appropriate and constructed knowledge. Therefore, reflecting and understanding on how knowledge is constructed entails the main object of current study and specifically, considering the manager work context and the changing nature of organizations, how information use impacts on knowledge construction. From a methodological perspective, it is featured as a longitudinal and contextual study, analyzed regarding the evaluation model of information activity. The study has focused its action on a plastics company located at State of Pernambuco, Brazil. The research noticed that the results of informational impact can evaluate the information use and its effect on decision taking, characterizing the informational process legitimacy; however the phenomenon must not be studied apart from its historical and organizational context. Keywords: Knowledge Construction. Informational Impact. Informational Efficacy. Information Use. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/3127/2468